Do sheep (Ovis aries) discriminate human emotional odors? - Izïa Larrigaldie; Fabrice Damon; Solène Mousqué; Bruno Patris; Léa Lansade; Benoist Schaal; Alexandra Destrez (Animal Cognition)
Abstract While sheep can detect and discriminate human emotions through visual and vocal cues, their reaction to human body odors remains unknown. The present study aimed to determine whether sheep (Ovis aries) can detect human odors, olfactorily discriminate stressed from non-stressed individuals, and behave accordingly based on the emotional valence of the odors. Axillary secretions from 34 students were collected following an oral examination (stress odor) or a regular class (non-stress odor). Fourteen female and 15 male lambs were then exposed to these odors through a habituation-dishabituation procedure. The habituation stimulus was presented four times for one minute, followed by the dishabituation stimulus presented once for one minute. Behavioral variables included spatiality relative to target odors, approach/withdrawal, ear positioning, sniffing, ingestion, and vocalization. Both female and male lambs more often positioned their ears backwards/forwards, and asymmetrically when exposed to the dishabituation stimulus, but regardless of their stress or non-stress value. They also changed their approach behavior when exposed to the dishabituation stimuli. Lambs displayed some behavioral signs of discrimination between the habituation and dishabituation odors, but regardless of their relation to stress or non-stress of human donors. In sum, this exploratory study suggests that young sheep respond negatively to the odor of unfamiliar humans, without showing any specific emotional contagion related to the stress odor. This exploratory study suggests young ovines can detect human body odor, a further step toward understanding the human-sheep relationship.